LA SEGURIDAD ALIMENTARIA NUTRICIONAL -SAN- UN ACERCAMIENTO A LA POLÍTICA PÚBLICA - Betancourt García, Mauricio (Cuadernos de Administración, 2006)
This presentation talks about an advance on the investigation about Nourishing and Nutritional Security -NNSin Colombia, which develops and critically  analyses the conceptual elements, related to the right to feeding, the eating sovereignty, the alimentary chain, the relations between health, feeding and nutrition, harmlessness, the regional and local development, the culture and NNS, the public policies and the environment; offering judgment elements that must be re-understood when getting incorporated in the design of the public policies, as well as the national, the regional, the departmental, the municipal or the local ones. When approaching the reflection facing the conditions of Nourishing and Nutritional Security in Colombia, the second chapter makes an aproximation from subjects refered to availability and stability; acces, use and utility, making reference to the alternatives to how the public policies of nourishing and alimentary security have been designed. The discussion aims to indicate elements of analysis that in the nourishing chain level must be articulated in the design of the public policy of NNS. The conditions that affect the availability and stability dinamics of foods in Colombia are analysed from: the levels of national production; the foreign trede import and exports; the public policy: in the environmental and economic dimensions of the national level and the departmental, regional and local one linked to the code and the environment; the high levels of concentration of the property; the international politic-social conflict that moves population of the countryside and, finally, the conflic of the use of ground between aptitude and use. It is facing these six conditions that must be implanted a dynamic of territorial development that integrates the public policies in the different orders.